Studi Deskriptif Pengetahuan Ibu tentang Toilet Training pada Anak Usia Toddler (1-3 Tahun) di Paud Terpadu Citra Indonesia Banjarbaru - Nova Uly Simbolon; Agustine Ramie; Hammad , (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2018)
Toilet training if not taught can cause children to be undisciplined, spoiled, and most importantly, children will experience psychological problems, children will feel different and cannot independently control defecation and urination. This study aims to determine the mother's knowledge about toilet training. The design of this study is descriptive. The study population was mothers who had toddler-age children (1-3 years) in Citra Integrated Integrated Education in Banjarbaru. Samples were taken using